2023
DOI: 10.1111/cbdd.14266
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in antifungal drug development targeting lanosterol 14α‐demethylase (CYP51): A comprehensive review with structural and molecular insights

Abstract: Fungal infections are posing serious threat to healthcare system due to emerging resistance among available antifungal agents. Among available antifungal agents in clinical practice, azoles (diazole, 1,2,4‐triazole and tetrazole) remained most effective and widely prescribed antifungal agents. Now their associated side effects and emerging resistance pattern raised a need of new and potent antifungal agents. Lanosterol 14α‐demethylase (CYP51) is responsible for the oxidative removal of 14α‐methyl group of ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 137 publications
0
4
0
Order By: Relevance
“…Antifungal drug resistance and the emergence of intrinsically resistant fungal strains and species to conventional drugs is a concerning threat that has been growing in recent years, 69 and the development of new antifungal drugs is paramount. 70 Based on our results, it is tempting to speculate that the combination of antifungal drugs with inhibitors of the N -linked mannosylation pathway may affect both biofilm formation and susceptibility to antifungal drugs. Currently, some drugs that inhibit enzymes of the protein N -linked glycosylation pathway in humans have been experimentally used, such as inhibitors of endoplasmic reticulum glycosidases.…”
Section: Discussionmentioning
confidence: 80%
“…Antifungal drug resistance and the emergence of intrinsically resistant fungal strains and species to conventional drugs is a concerning threat that has been growing in recent years, 69 and the development of new antifungal drugs is paramount. 70 Based on our results, it is tempting to speculate that the combination of antifungal drugs with inhibitors of the N -linked mannosylation pathway may affect both biofilm formation and susceptibility to antifungal drugs. Currently, some drugs that inhibit enzymes of the protein N -linked glycosylation pathway in humans have been experimentally used, such as inhibitors of endoplasmic reticulum glycosidases.…”
Section: Discussionmentioning
confidence: 80%
“…Lanosterol is converted to zymosterol via two intermediates, 4,4-dimethyl-zymosterol-8,14,24-trienol and 4,4-dimethyl-zymosterol, by lanosterol 14α-demethylase (ERG11) and sterol C14-reductase (ERG24). Azoles were identified as effective inhibitors of ERG11 (Table 5) via selective coordination with heme iron [397,398] and demonstrated striking antifungal activity against a variety of human fungal pathogens [399,400]. Importantly, azoles inhibit human lanosterol 14α-demethylase at substantially higher concentrations than the fungal enzyme [397].…”
Section: Ergosterol Synthesismentioning
confidence: 99%
“…14 Among these, fluconazole and voriconazole have been extensively used for the management of C. albicans infections for their ability to interrupt the biosynthesis of ergosterol, a key fungal-specific membrane sterol, by targeting and inhibiting the lanosterol 14α-demethylase (CYP51), a cytochrome P450 enzyme that catalyzes a key step reaction on the pathway of the conversion of lanosterol to ergosterol, encoded by the ERG11 (Cyp51) gene. 15 However, in recent years, the emergence of azoles resistance due to the mutation of drug target genes ERG11 and ERG3, 16 the upregulation of drug efflux genes CDR1 and CDR2 alongside the side effects of the available antifungals showed that a knowledge void persists in the search for novel antifungal agents effective against resistant antifungal strains, especially nonazole compounds targeting key steps of ergosterol biosynthesis. 17,18 The quest for expanding the antifungal toolbox should focus on the identification of new chemical entities acting as antifungal agents, but it should also not neglect the possibility to discover new compounds able to synergize their activity on resistant fungal strains.…”
Section: ■ Introductionmentioning
confidence: 99%